Study of temperature dependence on mercury solubility in condensate and crude oil : part II Cyclic aliphatic and aromatic hydrocarbons - Piya Kittichaichana (Chulalongkorn University, 2014)
Thesis (M.Sc.) -- Chulalongkorn University, 2006